ナンキョク エンガン カイヨウジョウ ノ キセツ サイクル - 大島, 慶一郎; オオシマ, ケイイチロウ; 滝沢, 隆俊; タキザワ, タカトシ; 牛尾, 収輝; ウシオ, シュウキ; 河村, 俊行; カワムラ, トシユキ; Ohshima, Kay I.; Takizawa, Takatoshi; Ushio, Shuki; Kawamura, Toshiyuki (1997)
P(論文) ACRのもとで, リュツォ・ホルム湾周辺において通年にわたる海洋観測を1990年-1992年の間行った。これらの観測によって, 低温・低塩・高溶存酸素で特徴づけられる南極冬季水の厚さが秋に最大(500m程度), 夏に最小(350-400m程度)になることが示された。この厚さの変化に伴って生じる比容の変化は岸での水位の季節変化の約1/3の変化分にしか相当しない。これは順圧の沿岸流が大きな季節変化をすることを示唆している。一方, 秋には冬季水層において著しい低塩化が起こる。これは前の夏に海氷融解によって表層が低塩化した冬季水が蓄積されたことによると考えられる。この低塩(従って低密度)水の蓄積がこの周辺の海域で南極底層水ができないことの理由の一つになっていると思われる。冬季水の厚さの季節変化は主に沿岸域での風の場の季節変化によることを提出した。すなわち, 沿岸域では卓越風である東風が強まる秋季に冬季水のエクマン収束が強化され, 東風が弱まる夏季にエクマン収束が弱まる, と考えた。 Under the Japanese Antarctic Climate Research (ACR) program, year-round oceanographic observations were conducted in the vicinity of Lutzow-Holm Bay, during 1990-1992. It was found that the thickness of the Winter Water (WW) layer, characterized by a cold fresh oxygen-rich water, exhibits its maximum in the austral fall (typically 500m) and its minimum in the austral summer (typically 350-400m). The associated density variation of the water column explains only about one third of the seasonal variations in sea level at the coast, which suggests a large seasonal variation in barotropic coastal flow. Prominent freshening occurs in the WW layer during fall. This appears to be caused by the accumulation of WW, whose upper portion is freshened in the preceding summer. We think that this accumulation of the freshened (accordingly less dense) water is a possible reason why bottom water formation can not occur in this area. We propose that the seasonal variation in the WW layer is mainly caused by the seasonal variation in the wind over the coastal ocean. In fall the prevailing easterly wind intensifies, which increases the Ekman convergence of WW in the coastal ocean, while in summer the opposite occurs. departmental bulletin paper